EXPLORING SERVANT LEADERSHIP ATTRIBUTES IN PRIVATE ISLAMIC SCHOOL TOWARDS A SUSTAINABLE SOCIAL ENTERPRISE - Roha Mohamed Noah,; Mohd Ali Bahari Abdul Kadir,; Ahmad Syahmi Ahmad Fadzil, (Journal of Islamic, Social, Economics and Development, 2023)
Social enterprise has emerged as an effective means of addressing social and environmental issues. Although model of servant leadership is developed, demonstrating how social entrepreneurs can wield power and control over their followers under the guise of social mission, creating social value, serving and empowering their followers, and empowering society. This study focuses on servant leadership attributes among entrepreneurs towards sustainability of social enterprises on Private Islamic School. The servant leadership style on social entrepreneurs is critically in this study. Insights are provided into how the concept of “service”, which is central to both social enterprise and servant leadership, can be another aspect of social entrepreneurs' soft and subtle power over their followers. However, research on the specific characteristics of social entrepreneurs is currently limited, and propositions regarding the influence of certain characteristics such as compassion, empathy, altruism, integrity, and honesty on social entrepreneurial behaviour have yet to be empirically tested. This study serves as a preliminary exploratory step for future research in this area by identifying a possible set of such attributes among servant leaders towards their social enterprises sustainability.